Performance Indicators of the Decision Support System in the Management of the University's Property Complex - Sadikova Sh. Sh. (International Journal on Orange Technologies, 2022)
In the context of assessing the effectiveness of the management of the property complex of a higher educational institution (university) the task of structuring the process of managing the university's fixed assets is formulated. The process is divided into three sublevels. A systematic analysis of existing indicators for assessing the effectiveness of the management of fixed assets has been carried out. The procedure for managing the property complex of the university has been formalized and the parameters of a rational solution to the management task have been identified. The conceptual structure of the decision support system for the management of the property complex of the university is constructed. A functional model of the system has been developed.